Preliminary evaluation of atomization characteristics of improved biodiesel for gas turbine application - Kumaran P.; Gopinathan M.; Razali N.M.; Kuperjans I.; Hariffin B.; Hamdan H. (Institute of Physics Publishing, 2023)
Biodiesel is one of the clean burning alternative fuels derived from natural resources and animal fats which is promising fuel for gas turbine application. However, inferior properties of biodiesel such as high viscosity, density and surface tension results in inferior atomization and high emission, hence impedes the fuel compatible for gas turbine application and emits slightly higher emission pollutants due to inferior atomization. This research work focuses on preliminary evaluation of the atomization characteristics of derived from Malaysian waste cooking oil which is the physical properties are subsequently improved by a microwave assisted post treatment scheme. The results shows with improvement in physical properties achieved through the post treatment, biodiesel exhibits significantly better atomization characteristics in terms of spray angle, spray length, sauter mean diameter and shorter evaporation time compared to the biodiesel before improvement and fossil diesel. Published under licence by IOP Publishing Ltd.